1991
DOI: 10.1093/ije/20.4.1010
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Diabetes Mellitus and Impaired Glucose Tolerance in the Middle-Aged Population of Three Areas in Finland

Abstract: The prevalence of diabetes mellitus and impaired glucose tolerance (IGT) was determined in a random sample of the population aged 45-64 years in three areas of Finland. The two-hour oral glucose tolerance test was repeated in subjects whose first test suggested abnormal glucose tolerance. In the final classification, based on the results of the two tests, the age-standardized prevalence of diabetes, according to the WHO criteria was 5.7% (95% confidence interval (CI): 4.3-7.1) in men and 4.6% (95% CI: 3.6-5.0)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
32
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 0 publications
7
32
1
Order By: Relevance
“…The latter authors, however, performed the glucose tolerance test twice, and reached their diagnoses of impaired glucose tolerance on the basis of abnormal findings in both, which will have lowered the number of persons with IGT Scand J Prim Health Care 1995: 13 considerably. The prevalence in our study is, nevertheless, higher than that found by Tuomilehto et al (12) in their first OGTT, and it is therefore possible that real differences in the prevalence of IGT may exist between different parts of Finland.…”
Section: Discussioncontrasting
confidence: 88%
See 2 more Smart Citations
“…The latter authors, however, performed the glucose tolerance test twice, and reached their diagnoses of impaired glucose tolerance on the basis of abnormal findings in both, which will have lowered the number of persons with IGT Scand J Prim Health Care 1995: 13 considerably. The prevalence in our study is, nevertheless, higher than that found by Tuomilehto et al (12) in their first OGTT, and it is therefore possible that real differences in the prevalence of IGT may exist between different parts of Finland.…”
Section: Discussioncontrasting
confidence: 88%
“…The findings, 9.9% of the men and 5.7% of the women with diabetes, c o n f w the earlier observations that diabetes mellitus is common in the middle-aged Finnish population (12). About half of the diabetic patients had not been diagnosed previously, and impaired glucose tolerance was quite common.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…A logistic CVD risk score will be developed which will be based on the prospective follow-up of subjects with IGT in a random population sample [29]. We will consider the following variables when developing the CVD risk score: blood pressure, serum total and HDL cholesterol, serum triglycerides, serum insulin, body mass index (BMI), waist and hip circumferences, sagittal and abdominal diameters, smoking and plasma glucose.…”
Section: Methodsmentioning
confidence: 99%
“…Half of the total cases with diabetes were previously undiagnosed [3]. Thus, the prevalence of abnormal glucose tolerance found in southern Germany is among the highest reported in European countries [4][5][6], emphasising the need for prevention. It has been shown that physical activity is one of the most important modifiable factors in the prevention of type 2 diabetes, because physical training, even in the absence of weight loss, can increase insulin sensitivity and improve glucose tolerance [7].…”
Section: Introductionmentioning
confidence: 99%